Gender-based food intake stereotype scale (GBFISS) for adolescents: development and psychometric evaluation - Rafael Monge-Rojas; Benjamín Reyes Fernández; Vanessa Smith-Castro (Health Psychology and Behavioral Medicine, 2020)
Objective. The study aimed to develop and test the validity and reliability of a gender-based food intake stereotype scale (GBFISS) to further the understanding of gender stereotype influences on food intake. Design. Two cross-sectional studies were conducted among adolescents. In the first one (n = 611), exploratory and confirmatory factor analyses were performed on subsamples to identify and cross-validate the scale’s structure. Evidence of concurrent validity (correlation with sexism) was also examined. In the second study (n = 813), confirmatory factor analysis was conducted to confirm the scale’s dimensionality on a different sample. Further evidence of construct validity (correlations with food intake and social desirability) was examined. Invariance was tested for different features as well. Main outcome. The Gender-Based Food Intake Stereotype Scale. Results. Factor analyses on the first and second studies helped identify and confirm the GBFISS as a three-dimensional scale. The studies also provided evidence of construct validity. Support for invariance by gender and age was found, and reliability was acceptable. Conclusion. The evidence suggests that the GBFISS is valid and reliable. Further research is recommended. The contribution of gender stereotypes, as measured by the GBFISS, to well-established health behavior models should be examined.